Additive manufacturing meta-functional composites for engineered bridge bearings: A review. (30th November 2020) - Sengsri, Pasakorn; Kaewunruen, Sakdirat
Highlights: Critical reviews of over 270 research articles related to bridge bearings have been conducted. Failure modes of bridge bearings are identified and prioritised. Alternative replacements of bridge bearings by composites is highlighted. Meta-functional composite bridge bearings via additive manufacturing (AM) technologies have been proposed. Insights stemming from this study underpin the industry adoption of AM technologies. Abstract: One of the most important causes of bridge failure is the design and structural deficiencies of bridge bearings. Recently, typical bridge bearings with the reinforcement of steel or fibre have been widely used in base isolation system. Especially for fibre-reinforced rubber bearings, they offer numerous benefits as higher stiffness and strength, more flexibility, and decrease of transport and fabrication costs. Under vibration, common bridge bearings cannot perform well and the materials used in the bearings cannot sustain under environmental conditions. To develop the performance of these common bearings to obtain their superior physical and mechanical properties (e.g. lightweight, higher stiffness, better impact resistence, and vibration attenuation), the use of metamaterials (periodic structures) in the bearings is considered for this reason. The current paper is the world's first to present a comprehensive, state-of-the-art overview of the development of meta-functional composites for bridge bearing applications, exposed to both static and dynamic conditions. Also, the paper shows an approach to fabricate meta-functional composite bridge bearings via additive manufacturing (AM) technologies. Furthermore, the numerical simulation has been conducted to enable new insights into the behavior of a meta-functional bridge bearing suitable for real-life practial applications. These insights are fundamental to the performance benchmarking including the development of vibration-based condition monitoring and inspection for predictive bridge component maintenance.